Overview of the different methods used in the primary culture of oral mucosa cells - Bryja, A; Popis, M; Borowiec, B; Dyszkiewicz-Konwińska, M; Kocherova, I; Angelova-Volponi, A; Mehr, K; Bruska, M; Nowicki, M; Kempisty, B (Journal of Biological Regulators & Homeostatic Agents, 2019)
The culture of primary cells in vitro has enabled to gain knowledge in the field of cell biology, disease mechanisms and to offer great potential in drug testing. To date, two main techniques of isolating and culturing oral mucosal cells, the direct explant method and the enzymatic method, dominate the literature and practice. In the present study, both techniques are discussed in detail, comparing the advantages and disadvantages of the two approaches in setting up a primary culture of oral mucosal cell. The direct explant technique is well-established and has been commonly used for the past 20-30 years. Although the method of setting up the cultures did not show much variations in the methodology described by authors, the culturing conditions varied according to the aims of the projects.
Keywords: Cells, Cultured; kultivované buňky; ústní sliznice; Humans; Mouth Mucosa; Primary Cell Culture; primární buněčná kultura; lidé